2015
DOI: 10.1371/journal.pone.0129737
|View full text |Cite
|
Sign up to set email alerts
|

Effect Modifying Role of Serum Calcium on Mortality-Predictability of PTH and Alkaline Phosphatase in Hemodialysis Patients: An Investigation Using Data from the Taiwan Renal Registry Data System from 2005 to 2012

Abstract: Predicting mortality in dialysis patients based on low intact parathyroid hormone levels is difficult, because aluminum intoxication, malnutrition, older age, race, diabetes, or peritoneal dialysis may influence these levels. We investigated the clinical implications of low parathyroid hormone levels in relation to the mortality of dialysis patients using sensitive, stratified, and adjusted models and a nationwide dialysis database. We analyzed data from 2005 to 2012 that were held on the Taiwan Renal Registry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
(32 reference statements)
0
13
1
Order By: Relevance
“…This finding deserves special consideration given the high incidence of chronic kidney disease-mineral and bone disorder (CKD-MBD) and the widespread use of calcium-based binders in hemodialysis patients. A growing number of studied have demonstrated that higher calcium levels are associated with higher mortality [31, 32]. It is possible that the impact of calcium levels on BPV is a mechanism underlying this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…This finding deserves special consideration given the high incidence of chronic kidney disease-mineral and bone disorder (CKD-MBD) and the widespread use of calcium-based binders in hemodialysis patients. A growing number of studied have demonstrated that higher calcium levels are associated with higher mortality [31, 32]. It is possible that the impact of calcium levels on BPV is a mechanism underlying this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that iPTH levels and the risk of death in HD patients show a J-curve relationship [4,13,14,15]. Recently, data from the Taiwan Renal Registry Data System showed that at any level of serum Ca or P, patients with low iPTH levels had higher mortality rates than those with normal or high iPTH levels [16]. However, some reports also found no association between low iPTH levels and mortality in HD patients [1,2,4,19,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…In general, patients with CKD who had higher levels of serum Ca, P, and iPTH were at an increased risk for death [3,4,13,14,15]. In contrast, a few reports demonstrated that low iPTH levels increase the mortality risk in patients with CKD [4,15,16]. Possible reasons for these variations in results among previous studies are (1) non-uniform management protocols in cohort studies, (2) variations in study participant demographics, and (3) difference in the statistical methods used.…”
Section: Introductionmentioning
confidence: 99%
“…In patients on dialysis, serum phosphorus levels have been shown to have a U-shaped association with mortality [2][3][4][5][6][7]. As for serum calcium levels, although it is not clear whether low levels are detrimental, high levels are known to be associated with a poor prognosis [3,4,8]. Given these background conditions, each guideline provides target values for serum phosphorus and calcium levels when managing patients on dialysis [1,9].…”
Section: Introductionmentioning
confidence: 99%